Casearia sylvestris na permeabilidade gástrica à sacarose em equinos submetidos a protocolo de indução de úlcera gástrica - Fialho, Sergio da Silva; Nogueira, Geison Morel; Duarte, Cláudia Acosta; Neto, Álvaro de Oliveira Paiva; Macoris, Delphim da Graça [UNESP] (My University, 2010)
Studies on laboratory animals suggest an antiulcergonic effect of Casearia sylvestris extract. This extract has not yet been tested for the prophylaxis and/or treatment of gastric ulcers in horses. In order to evaluate the influence of C. sylvestris extract on gastric sucrose permeability, six adult horses underwent a protocol of gastric ulcer induction. All animals were submitted to sucrose permeability testing before and at the end of gastric ulcers induction by intermittent feed deprivation, for detection of gastric ulcers. During the seven days of induction, the animals were submitted to daily treatment by nasogastric tubing with C. sylvestris extract (9mg kg-1 b.w.) or vehicle (Agar). After 32 days of pasture turnout, in order to allow healing of induced ulcers, each animal underwent a second induction protocol, in which treatments were alternated. By this manner, each animal was submitted to both treatments in distinct periods. The urine sucrose concentration was determined for each sample obtained, by high performance liquid chromatography and pulsed amperometric detection. No alterations in clinical examination and hemograms were detected. Treatment with C. sylvestris extract avoided the increase on urine sucrose concentration (P<0.05) when compared to the vehicle, suggesting an antiulcer preventive effect for equine gastric ulcers. More extensive studies including gastroscopy are necessary to evaluate the possibility of employing this extract for the prophylaxis and/or treatment of gastric ulcers in horses.
Casearia sylvestris on gastric permeability to sucrose in horses submitted to gastric ulcer induction protocol
Keywords: Casearia sylvestris; Equine; Gastritis; Stomach